Artificial intelligence in digital service ecosystems—Towards a taxonomy and archetypes - Hansmeier, Philipp; Schäfer, Jannika Marie; zur Heiden, Philipp (Electronic Markets)
Traditional dyadic customer-provider interactions are being shifted to polyadic interactions involving diverse participants in digital service ecosystems. Especially, artificial intelligence (AI) is increasingly integrated into these ecosystems, so that they comprise non-human participants (e.g., AI-based chatbots)—fundamentally altering the nature of value (co-)creation. While existing literature examines human-to-human interactions, knowledge of service interactions between human actors and AI-based systems is still underexplored. To address this research gap, we develop a taxonomy, comprising six iterations, that explores the peculiarities of AI as either a resource or a (non-human) agent in digital service ecosystems. We evaluate our taxonomy using a multiple case study and derive the four archetypes of AI in digital service ecosystems: (1) discriminative experience enhancer, (2) protective ecosystem orchestrator, (3) ecosystem innovation companion, and (4) personalized service composer. Our results extend the knowledge on service science by showing how AI-based systems—discriminative or generative, and focusing on the interaction in the ecosystem or the individual service encounter—assume the role of resources and non-human agents. Researchers and practitioners can utilize our results to augment their ecosystems with AI.

Decentring the governance of AI in the military: a focus on the postcolonial subject - Bhila, Ishmael (AI and Ethics)
The governance of emerging technologies with increased autonomy in the military has become a topical issue in recent years, especially considering the rapid advances in artificial intelligence and related innovations in computer science. Despite this hype, the postcolonial subject’s position has been seen as secondary, often associated with victimhood or obscurity. By shifting the narrative to highlight the postcolonial subject’s agency—not only in providing real-world examples of artificial intelligence use in the military but also in knowledge creation and shaping the discourse on governance within the international, this paper contributes to an area of research that is often overlooked. The paper unpacks the norm-making efforts of postcolonial subjects regarding emerging military technologies. In doing this, the paper aims to advance postcolonial theory by showing how the dynamics of governing emerging military technologies intertwine with postcolonial subjectivity and to broaden the academic discussion on the governance of emerging military technologies and algorithmic violence, which has so far been dominated by Western or universalistic discourse.

Praxisschock oder Kohärenz? – Retrospektive Einschätzungen von Berufseinsteiger*innen zu den Phasen der Lehrkräftebildung - Homt, Martina

Behind the Mask: Investigating the Influence of Pseudonymity on Polarization Dynamics in Social Virtual Reality - Tölle, Laura; Rose, Robert; Trier, Matthias

Social Support and Emotional Expression – Exploring Online Community Polarization Dynamics: The Case of Borussia Dortmund - Tölle, Laura; Trier, Matthias

Content Themes and Self-Presentation of Virtual Influencers - Tölle, Laura; Rehmer, Torben; Ruppel, Fynn; Müller, Johann; Trier, Matthias

The Schrödinger equation with fractional Laplacian on hyperbolic spaces and homogeneous trees - Palmirotta, Guendalina; Sire, Yannick; Anker, Jean-Philippe (Journal of Differential Equations)
We investigate dispersive and Strichartz estimates for the Schrödinger equation involving the fractional Laplacian in real hyperbolic spaces and their discrete analogues, homogeneous trees. Due to the Knapp phenomenon, the Strichartz estimates on Euclidean spaces for the fractional Laplacian exhibit loss of derivatives. A similar phenomenon appears on real hyperbolic spaces. However, such a loss disappears on homogeneous trees, due to the triviality of the estimates for small times.
Keywords: Schrödinger equation; Fractional Laplacian; Dispersive estimates; Strichartz estimates; Real hyperbolic spaces; Homogeneous trees

Patterson-Sullivan distributions of finite regular graphs - Arends, Christian; Palmirotta, Guendalina (arXiv:2603.09779)
On finite regular graphs, we construct Patterson-Sullivan distributions associated with eigenfunctions of the discrete Laplace operator via their boundary values on the phase space. These distributions are closely related to Wigner distributions defined via a pseudo-differential calculus on graphs, which appear naturally in the study of quantum chaos. Using a pairing formula, we prove that Patterson-Sullivan distributions are also related to invariant Ruelle distributions arising from the transfer operator of the geodesic flow on the shift space. Both relationships provide discrete analogues of results for compact hyperbolic surfaces obtained by Anantharaman-Zelditch and by Guillarmou-Hilgert-Weich.

Predictors of primary school students’ prosocial behaviour toward peers with social-emotional difficulties in inclusive education: Insights from the Theory of Planned Behaviour. Individual Paper Presentation. EARLI SIG 15 Biennial Conference 2026 ‘Special Educational Needs’. “Research methodological approaches bridging special educational needs”. (accepted) - Löper, Marwin Felix; Knickenberg, Margarita; Hellmich, Frank

Social and emotional competencies for cooperative learning in inclusive primary education: A project overview. Poster Presentation. EARLI SIG 15 Biennial Conference 2026 ‘Special Educational Needs’. “Research methodological approaches bridging special educational needs”. (accepted) - Casamassima, Gianna; Funk, Michael; Knickenberg, Margarita; Löper, Marwin Felix; Grosche, M.; Zimmer, L.; Grüßing, M.; Wess, N.; Hellmich, Frank

Teachers’ conceptualizations of social-emotional competencies in cooperative learning: Insights from inclusive primary school classrooms. Individual Paper Presentation. EARLI SIG 15 Biennial Conference 2026 ‘Special Educational Needs’. “Research methodological approaches bridging special educational needs”. (accepted) - Knickenberg, Margarita; Funk, Michael; Casamassima, Gianna; Löper, Marwin Felix; Hellmich, Frank

Fiber-matrix adhesion in glass fiber reinforced thermoplastic composite laminates and its effect on mechanical properties - Moritzer, Elmar; Brandes, Philipp; Wittler, Maurice; Claes, Leander; Wippermann, Mareen; Haag, Markus; Gries, Thomas; Henning, Bernd (International Polymer Processing)
Abstract With the growing demand for lightweight solutions to reduce emissions, especially in the transportation, automotive and aerospace sectors, recyclable, continuous fiber-reinforced plastic composite laminates with a thermoplastic matrix are of rising interest. To achieve their maximum mechanical properties, the fiber-matrix adhesion (FMA) is critical. In this work, continuous fiber-reinforced thermoplastic laminates (CFRTPL) with a polypropylene (PP) matrix and twill woven glass fiber fabrics are produced by film stacking. The films used contain different amounts of maleic-anhydride-grafted PP (MA-g-PP) as a coupling agent to produce CFRTPL of different mechanical strengths. To analyze the FMA, the CFRTPL are subjected to Charpy-impact and tensile tests. Additionally, single fiber pull-out tests (SFPT) are conducted to further investigate the effect of MA-g-PP on the FMA. The results of the SFPT show an improvement in apparent interfacial shear strength (AIFSS) when the MA-g-PP content is increased, which can be attributed to an increase in FMA. However, the research shows that MA-g-PP has a low impact on the mechanical properties if the force is applied parallel to the warp and weft threads during tensile testing and the results of the Charpy-impact testing suffer from embrittlement of the matrix material. Subsequently, the results of this study are compared to three-point flexural tests conducted in a previous study. It can be concluded that tensile and impact tests are not suited to investigate FMA on a macroscopic scale, while SFPT and flexural tests provide a better alternative.

Zum Umgang mit persönlicher Betroffenheit im Pädagogikunterricht. Perspektiven und Handlungsstrategien von Pädagogiklehrkräften - und für sie - Hanke, Jule Lara; Schwarz, Lea Marie; Engemann, Mario (Zeitschrift PädagogikUNTERRICHT)

Cells on Autopilot: Adaptive Cell (Re)Selection via Reinforcement Learning - Illian, Marvin; Khalili, Ramin; Rocha, Antonio A. de A.; Wang, Lin (arXiv:2601.04083)
The widespread deployment of 5G networks, together with the coexistence of 4G/LTE networks, provides mobile devices a diverse set of candidate cells to connect to. However, associating mobile devices to cells to maximize overall network performance, a.k.a. cell (re)selection, remains a key challenge for mobile operators. Today, cell (re)selection parameters are typically configured manually based on operator experience and rarely adapted to dynamic network conditions. In this work, we ask: Can an agent automatically learn and adapt cell (re)selection parameters to consistently improve network performance? We present a reinforcement learning (RL)-based framework called CellPilot that adaptively tunes cell (re)selection parameters by learning spatiotemporal patterns of mobile network dynamics. Our study with real-world data demonstrates that even a lightweight RL agent can outperform conventional heuristic reconfigurations by up to 167%, while generalizing effectively across different network scenarios. These results indicate that data-driven approaches can significantly improve cell (re)selection configurations and enhance mobile network performance.

Breaking the Ice: Analyzing Cold Start Latency in vLLM - Shaaban KabakiboKabakibo, Huzaifa; Trivedi, Animesh; Wang, Lin (The 9th Annual Conference on Machine Learning and Systems (MLSys))

Before the First Token: Benchmarking Data Preprocessing in Vision-Language Models - Zohdi, Sepideh; Wang, Lin (The 6th Workshop on Machine Learning and Systems (EuroMLSys))

Cells on Autopilot: Adaptive Cell (Re)Selection via Reinforcement Learning - Illian, Marvin; Khalili, Ramin; A. de A. Rocha, Antonio; Wang, Lin (2026 24th International Symposium on Modeling and Optimization in Mobile, Ad Hoc, and Wireless Networks (WiOpt))

Reinforcement Learning: A Comprehensive Open-Source Course - Abdelwanis, Ali Hassan Ali; Haucke-Korber, Barnabas; Jakobeit, Darius; Kirchgässner, Wilhelm; Meyer, Marvin; Schenke, Maximilian; Vater, Hendrik; Wallscheid, Oliver; Weber, Daniel (Journal of Open Source Education)

Spectral theory for transfer operators on compact quotients of Euclidean buildings - Hilgert, Joachim; Kahl, Daniel; Weich, Tobias (arXiv:2603.26949)
In this paper we generalize the geodesic flow on (finite) homogeneous graphs to a multiparameter flow on compact quotients of Euclidean buildings. Then we study the joint spectra of the associated transfer operators acting on suitable Lipschitz spaces. The main result says that outside an arbitrarily small neighborhood of zero in the set of spectral parameters the Taylor spectrum of the commuting family of transfer operators is contained in the joint point spectrum.

Using Attack and Failure Propagation Analysis for Context-Aware Security Control Suggestions - Trentinaglia, Roman; Koch, Thorsten; Bodden, Eric (Proceedings of the 14th International Conference on Model-Based Software and Systems Engineering)